Fatty Acid Composition of Mature Breast Milk in Malay Women from Kuala Lumpur, Malaysia - Haron, Hasnah; Lee, Jyy Ni; Abd Rahman, Rahana; Hamzaid, Nur Hana; Law, Chai Jia; Bibus, Douglas; W. Solomons, Noel; B Rolker, Heike (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to determine the Fatty Acid (FA) composition in human mature milk and the relationship between essential FA levels in breast milk and maternal dietary intake during postpartum period. This study enrolled seventeen exclusively breastfeeding women with full-term, disease-free babies (26‒64 days). Milk samples were collected using Absorbent Spot Cards. Subsequently, gas chromatography was performed to analyze FA composition. The total FA constituted saturated fatty acids (40.56±2.62%), monounsaturated fatty acids (43.54±2.60%), and polyunsaturated fatty acids (14.01±1.34%). No relationship was observed between maternal dietary omega-3 FA intake and human milk omega-3 content. These findings suggest that humans have a reservoir to store FA for babies during pregnancy and that omega-3 content in human milk was not influenced by postpartum maternal diet. It highlights the importance of maternal diet during pregnancy for optimal fatty acid levels in breast milk.